Police officers' use of evidence to elicit admissions in a fictitious criminal case. Issue 1 (23rd August 2016) - Tekin, Serra; Granhag, Pär Anders; Strömwall, Leif A.; Vrij, Aldert
Abstract: We examined how police officers planned to interview suspects in a situation where they lacked information about a critical phase of a crime (i.e., the time during which the crime took place) but possessed information about less critical phases of the crime (i.e., the time before and/or after the crime took place). The main focus was the officers' planned use of the available information (evidence) to elicit admissions about the critical phase. A survey was distributed to police officers ( n = 69) containing a fictitious murder case for which they were to prepare an interview with a suspect. The investigators planned to disclose the evidence more often in a strategic manner (obtaining the suspect's statement and exhausting alternative scenarios before revealing the evidence) than in a non‐strategic manner (revealing the evidence before requiring an explanation). The investigators' most frequently reported reason for their planned evidence use was to collect additional information about the particular phase to which the disclosed evidence pertained. It was rare that the investigators planned to disclose the evidence about a less critical phase of the crime in order to elicit admissions about the more critical phase (e.g., by disclosing the evidence to try to shift the suspect's counter‐interrogation strategy from less to more forthcoming). The investigators may benefit from recent research showing that strategic evidence disclosure can be used as a means to elicit admissions about a phase of a crime for which information is lacking.